The Influence of Service Quality and Customer Satisfaction on Customer Loyalty at Mak Lin Sibolga Cassava Chili Chips Business - Martiani Telaumbanua; Mhd. Shafwan Koto; Andrian Irsyan (Journal of Economics, Management and Accounting (JEMA), 2026)
This study aims to determine the effect of service quality and customer satisfaction on customer loyalty at the Mak Lin Sibolga Cassava Chili Chips Business. This research uses an explanatory research design with a quantitative approach. The population in this study consisted of customers of the Mak Lin Sibolga Cassava Chili Chips Business, with a sample of 48 respondents obtained through questionnaire distribution. The results of the study indicate that partially, service quality has a positive and significant effect on customer loyalty with a t-value of 3.957 > t-table of 2.014 and a significance value of 0.001 < 0.05. Customer satisfaction also has a positive and significant effect on customer loyalty with a t-value of 2.974 > t-table of 2.014 and a significance value of 0.005 < 0.05. Simultaneously, service quality and customer satisfaction have a positive and significant effect on customer loyalty with an F-value of 37.604 > F-table of 3.20 and a significance value of 0.001 < 0.05. Therefore, it can be concluded that improving service quality and customer satisfaction can increase customer loyalty at the Mak Lin Sibolga Cassava Chili Chips Business.